2022
DOI: 10.3390/molecules27165086
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol Derivatives, Bearing 3,5-Disubstituted Isoxazole and 1,4-Disubstituted Triazole, as Potential Antileukemia Agents by Promoting Apoptosis

Abstract: In the present study, we assess tyrosol derivatives bearing 3,5-disubstituted isoxazoles and 1,4-disubstituted triazoles for their ability to inhibit the proliferation of K562 cells derived from leukemia as well as primary chronic myeloid leukemia (CML) cells obtained from the peripheral blood of 15 CML patients including 10 patients with untreated chronic phase and 5 patients with resistance against imatinib or multiple TKI. Our results showed that most derivatives displayed significant anti-proliferative act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the other hand, the drug-induced oxidative stress exaggeration in leukemic cells could intensify the genotoxic effects of conventional therapy, facilitating the activation of programmed cell death ( Yang et al, 2018 ). In fact, recent findings showed that the stimulation of oxidative stress in CML, using compounds such as tyrosol derivatives, verbascoside, and zerumbone, promotes mitochondrial membrane potential dissipation, caspase activation, and apoptosis ( Rajan et al, 2015 ; Abdelkafi-Koubaa et al, 2022 ; Akgun-Cagliyan et al, 2022 ). Therefore, the strategy of deliberately increasing ROS to cytotoxic levels for leukemia cells seems to be very appealing, and our data are in agreement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the drug-induced oxidative stress exaggeration in leukemic cells could intensify the genotoxic effects of conventional therapy, facilitating the activation of programmed cell death ( Yang et al, 2018 ). In fact, recent findings showed that the stimulation of oxidative stress in CML, using compounds such as tyrosol derivatives, verbascoside, and zerumbone, promotes mitochondrial membrane potential dissipation, caspase activation, and apoptosis ( Rajan et al, 2015 ; Abdelkafi-Koubaa et al, 2022 ; Akgun-Cagliyan et al, 2022 ). Therefore, the strategy of deliberately increasing ROS to cytotoxic levels for leukemia cells seems to be very appealing, and our data are in agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, the combination of biologically interesting core structural motifs [ 24 , 25 ], such as the triazole, with a further heterocyclic nucleus holds therapeutic properties in a variety of fields, including combating microbial pathogens [ 26 ]. Particularly, diversely substituted triazole/isoxazole conjugates have shown enhanced biological activities [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%